4t+9=(-8)-13

Simple and best practice solution for 4t+9=(-8)-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4t+9=(-8)-13 equation:


Simplifying
4t + 9 = (-8) + -13

Reorder the terms:
9 + 4t = (-8) + -13
9 + 4t = -8 + -13

Combine like terms: -8 + -13 = -21
9 + 4t = -21

Solving
9 + 4t = -21

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 4t = -21 + -9

Combine like terms: 9 + -9 = 0
0 + 4t = -21 + -9
4t = -21 + -9

Combine like terms: -21 + -9 = -30
4t = -30

Divide each side by '4'.
t = -7.5

Simplifying
t = -7.5

See similar equations:

| 242=x+5-22 | | 405xy+245x^2= | | 6x+308= | | 5x+6x+2+2=3x+5+7x | | -9x-13+11x-25=2 | | (-10)7= | | f(x)=3e^5x | | 100-2P=40+2P | | 100-2P=40 | | log(x+5)=ln(x-3) | | m^2-5m+14=0 | | 5(2x-8)-7x=x+6 | | 40y^9+5y^4= | | 8x-3y+4=0 | | (-1)211= | | 12-m=2m | | 23=7x+3-2x | | y=4x+3x | | 48=x+9+2x | | .6x-.1=4 | | 0=5-n-7 | | 6m-17=-17+2m | | 4x+y=2000000 | | 15x-3=3x-75 | | =hb | | 36y^8+4y^3= | | 12-3(4x-1)=5 | | 3*x^2+7x-15= | | 0.2x-8=-2+x | | tan(x)=20 | | -23x+4y=72 | | 6=5x-2x+3 |

Equations solver categories